Monocyte Metabolism and Function in Patients Undergoing Cardiac Surgery - Mayer, Daniel; Altvater, Marc; Schenz, Judith; Arif, Rawa; Karck, Matthias; Leuschner, Florian; Weigand, Markus A.; Uhle, Florian; Lichtenstern, Christoph (Frontiers in Cardiovascular Medicine, 2022)
Objective Cardiopulmonary bypass (CPB) can lead to a systemic inflammation, which is associated with higher morbidity. Therefore, we investigated the metabolism of isolated blood monocytes before and after CPB in comparison to healthy controls. Methods In this prospective, monocentric, observational study, we included 30 patients undergoing CPB and 20 controls. We isolated monocytes from heparinized blood and investigated their metabolism by using Seahorse technology before (t0), four hours (t4) and 24 hours (t24) after the start of the CPB. We also examined PD-L1 (Programmed Cell Death 1 Ligand), PD-L2, VISTA (V-Domain Ig Suppressor of T Cell Activation) and HLA-DR (Human Leukocyte Antigen – DR Isotype) using Fluorescence-activated Cell Sorting analysis. Additionally, we investigated plasma cytokine levels in patients without and after ex-vivo stimulation. Results CPB induced inflammatory responses are shown by significantly elevated plasma Interleukin-6 levels in the CPB-group compared to baseline and controls (t0: 0 pg/ml (95% CI 0-0 pg/ml); t4: 163.2 pg/ml (95% CI: 100.2-107.3 pg/ml), p<0.0001; t24: 110.7 pg/ml (95% CI: 97.2-160.7 pg/ml), p<0.0001 and Controls: 0 pg/ml (95% CI 0-0 pg/ml)). The cytokine release in the ex-vivo stimulation is reduced for Lipopolysaccharide stimulation at t4 (t0: 35676 pg/ml (95% CI: 22171-46568 pg/ml) vs. t4: 15021 (95% CI 10245-24780 pg/ml), p<0.0001). Intracellular metabolism of monocytes after CPB showed a protracted shift to aerobic glycolysis (t0: 179.2 pmol/min (95% CI 138.0-205.1 pmol/min) vs t24: 250.1 pmol/min (95% CI 194.8-300.2 pmol/min), p<0.0001). Additionally, we observed an altered metabolism in monocytes in cardiac surgery patients compared to controls even before any surgical procedure (t0: 179.1 pmol/min (95% CI 138.0-205.1) vs controls 97.4 (95% CI 59.13-144.6 pmol/min), p=0.0031). Conclusion After CPB, patients’ monocytes show a shift in metabolism from oxidative phosphorylation to aerobic glycolysis, which is associated with energy-demanding and proinflammatory processes. This is the first study to show changes in monocyte immunometabolism in cardiac surgery. Monocytes of patients undergoing cardiac surgery were leaning towards aerobic glycolysis even before any surgical procedure was conducted. Leaving the question of the pathophysiological mechanisms for future studies to be investigated and paving the way for potential therapy approaches preventing inflammatory effects of CPB.